Adenosine A2a Receptor Regulates Autophagy Flux and Apoptosis to Alleviate Ischemia-Reperfusion Injury via the cAMP/PKA Signaling Pathway - Xia, Yun; He, Feng; Moukeila Yacouba, Mohamed Bassirou; Zhou, Huimin; Li, Jingfan; Xiong, Ying; Zhang, Jingjing; Li, Hui; Wang, Yanlin; Ke, Jianjuan (Frontiers in Cardiovascular Medicine, 2022)
Exploring effective methods to lessen myocardial ischemia-reperfusion injury still has positive significance. The adenosine A2a receptor (A2aR) has played a crucial part in cardiac ischemia-reperfusion injury. Previous studies revealed that the adenosine A2a receptor regulated autophagy, but the specific mechanism in myocardial ischemia-reperfusion injury was still unclear. We established an ischemia-reperfusion model (30 minutes of ischemia and 2 hours of reperfusion) in vivo and a model with oxygen-glucose deprivation for 6 hours and reoxygenation for 18 hours (OGDR) in vitro. The ischemia-reperfusion injury resulted in prolonged QTc interval, left ventricular systolic dysfunction, and myocardial infarction. In vitro model, we found that the OGDR-induced autophagosomes and apoptosis caused myocardial cell death, as evidenced by a significant increase in the generation of lactate dehydrogenase and creatine kinase-MB. Furthermore, overactivated autophagy with rapamycin showed an anti-apoptotic effect. The interaction between autophagy and apoptosis in myocardial ischemia-reperfusion injury was complex and variable. We discovered that the activation of adenosine A2a receptor could promote the expression of Bcl-2 to inhibit the levels of Beclin-1 and LC3II. The number of autophagosomes exceeded that of autolysosomes under OGDR, but the result reversed after A2aR activation. Activated A2aR with its agonist CGS21680 before reperfusion saved cellular survival through anti-apoptosis and anti-autophagy effect, thus improving ventricular contraction disorders, and visibly reducing myocardial infarction size. The myocardial protection of adenosine A2a receptor after ischemia may involve the cAMP-PKA signaling pathway and the interaction of Bcl-2-Beclin-1.